Delayed pneumothorax after CT-guided percutaneous fine needle aspiration lung biopsy. Issue 6 (June 1997) - Traill, Z C; Gleeson, F V
Abstract : Two patients are described who developed pneumothoraces more than 24 hours after computed tomography (CT) guided percutaneous fine needle aspiration lung biopsies. The pneumothoraces required treatment in both cases. Such delayed pneumothorax after lung biopsy is extremely unusual. Patients should be warned of the possible occurrence of this complication and instructed to seek medical help if they develop chest pain or breathlessness.